Double chamber cross‐talk, the ultimate double‐cross. Issue 12 (20th July 2020) - Almehmadi, Fahad; Duffett, Stephen; Khan, Habib R.; Klein, George; Yee, Raymond
Abstract: Cross‐talk is a well‐described phenomenon in a dual‐chamber cardiovascular implantable electronic device. Far‐field ventricular events are more commonly sensed in the atrial channel, the reverse is uncommon, and seeing both at the same time has never been reported. We present a case of double cross‐talk in a dual‐chamber Medtronic ® implantable cardioverter‐defibrillator. In this report, we decipher an unusual device response to the cross‐talk and describe the programming changes required to resolve it.